Entrenamiento en estrategias cognitivo-conductuales de afrontamiento de los síntomas depresivos para aumentar niveles de adherencia al tratamiento en pacientes con insuficiencia renal crónica de la Unidad Renal DialIbarra de la ciudad de Ibarra - Quintana Silva, Karla Sofía (2016)
This systematization of experience will inform the development and results of cognitive restructuring training undertaken in patients with chronic renal failure, who has depressive symptoms and low adherence to medical treatment, in order to reduce depressive symptoms and improve the level of adherence treatment. The training was held weekly in the Renal Unit DialIbarra located in Ibarra City and was based on group sessions in which beneficiaries patients were trained in cognitive restructuring techniques. The group was conformed by fourteen patients, which were selected according to inclusion and exclusion criteria and voluntary acept to be participants in the project. Twelve group sessions were developed during the three months of intervention, in which three sessions were focused exclusively on cognitive restructuring training of cognitive distortion catastrophic vision. These three sessions are those that are systematized chronologically in this report. In addition was develop and evaluation about psychological and physiological variables intervened, before and after the intervention, with the objetive to demonstrat the impact of the project. After the intervention positive results such as improved mood and reduced depressive symptoms of the participants was obtained also substantially it reduced the rate of cognitive distortions, and thereby the grip level improved medical treatment and the quality of life of patients and their families are promoted.